TEST OF STIMULATIVE EFFECTS GENERATED BY SOME DRUGS ON THE SYMPATIC AND PARASYMATIC NERVE SYSTEMS IN TRIED ANIMALS - Silvani urfin sini (Jurnal Ilmiah dr. Aloei Saboe, 2023)
This study aims to determine the anatomy of nerve cells, especially the autonomic nervous system, and to distinguish the effects of stimulation and inhibition of the sympathetic and parsympathetic nervous systems, which are nervous systems that work under the autonomic nervous system. In experimental animals, mice and mice were given several drugs belonging to the cholinergic drug class in the form of metochlorpramide, pilocaprin and adrenaline which would inhibit or have different effects and activities. The method used in this study is a laboratory experimental method using 4 experimental animals, namely 3 males and 1 female mice, where each mouse is given drug treatment by injecting intra-peritoneally and orally. The results obtained showed that after administration of several drugs, namely metoclopramide, pilocarpine and adrenaline, showed that these drugs had an effect on the autonomic nervous system or an effect commonly felt by experimental animals. The effects felt on the autonomic nervous system include tremor, diameter, dieresis, miosis, saliva and vasodilation at different time intervals.